Analisis Resiko Bahaya Ergonomi Menggunakan Acuan SNI 9011:2021 pada Pekerja Ojek Online di Stasiun Gubeng Surabaya - Laili Faizatul Mahgfiroh; Ratria Zahra Firnanda Sari; Restu Widodo; Denny Oktavina Radianto (CV. KAMPUS AKADEMIK PUBLISING, 2024)
In this era where everything is integrated with technology, it can make it easier for everyone to get a job, one of which is the online motorcycle taxi application. However, online motorcycle taxi workers often have GOTRAK complaints. Therefore, the aim of this journal is to analyze GOTRAK complaints from online motorcycle taxi workers using the SNI 9011:2021 reference, as well as provide recommendations for reducing GOTRAK complaints from online motorcycle taxis.